EFEKTIFITAS PENGOLAHAN AIR EFFLUENT MENJADI AIR REKLAMASI DI INSTALASI PENGOLAHAN AIR LIMBAH SUWUNG DENPASAR DITINJAU DARI KANDUNGAN KEKERUHAN, TOTAL ZAT TERLARUT (TDS), DAN TOTAL ZAT TERSUSPENSI (TSS) - Luh Putu Widya Kalfika Devi; K. G. Dharma Putra; A. A. Bawa Putra (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2013)
The application of water reclamation system has been researched for the concentrations of Total Suspended Solid (TSS), Total Dissolved Solid (TDS), and turbidity in the effluent of waste water treatment in Suwung Denpasar. The aims of the research are to determine the effect of each stage of water reclamation, to determine the effectiveness water reclamation system and to know the quality reclaimed water. The results showed that each stage of water reclamation system can decrease the concentrations of TSS, TDS, and turbidity from effluent. The percentage of reduction of TSS, TDS, and turbidity in biological filtration system were 85.60 %, 63.75 %, and 62.78 % respectively. The pre-ozonation system were 63.82 %, 64.93 %, and 73.78 % respectively and the coagulation and membrane systems were 60.58 %, 92.48 %, dan 74.58 % respectively. The overall rate of effectivenes of waste water reclamation system was 97.94% for TSS, 99.04% for TDS and 97.52% for turbidity.